2012
DOI: 10.1136/jclinpath-2012-201194
|View full text |Cite
|
Sign up to set email alerts
|

EGFRmutation testing in lung cancer: a review of available methods and their use for analysis of tumour tissue and cytology samples

Abstract: AimsActivating mutations in the gene encoding epidermal growth factor receptor (EGFR) can confer sensitivity to EGFR tyrosine kinase inhibitors such as gefitinib in patients with advanced non-small-cell lung cancer. Testing for mutations in EGFR is therefore an important step in the treatment-decision pathway. We reviewed reported methods for EGFR mutation testing in patients with lung cancer, initially focusing on studies involving standard tumour tissue samples. We also evaluated data on the use of cytology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
226
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(238 citation statements)
references
References 90 publications
7
226
0
3
Order By: Relevance
“…A recent systematic review 28 identified by the literature search has indicated that numerous studies have been published showing excellent performance of smear preparations, such that this preference is no longer appropriate. It is incumbent upon any laboratory that tests cytopathology specimens to perform appropriate validation studies of these as separate sample types, distinct from tissue and blood samples.…”
Section: Any Cytology Sample With Adequate Cellularity and Preservatimentioning
confidence: 99%
“…A recent systematic review 28 identified by the literature search has indicated that numerous studies have been published showing excellent performance of smear preparations, such that this preference is no longer appropriate. It is incumbent upon any laboratory that tests cytopathology specimens to perform appropriate validation studies of these as separate sample types, distinct from tissue and blood samples.…”
Section: Any Cytology Sample With Adequate Cellularity and Preservatimentioning
confidence: 99%
“…The utility of cytology samples in detecting mutations in lung cancer have recently been increased and relatively widely investigated (8,(30)(31)(32). Cytology samples are especially useful in The present study showed that cytology specimens are comparable, or even better than non-cytology specimens, in detecting both EGFR and KRAS mutations.…”
Section: Discussionmentioning
confidence: 48%
“…The discovery of cancer-related driver molecular abnormalities have led to the development of efficient targeted therapies. Recent advances in understanding of the complex biology of LC, particularly of the activation of oncogenes by EGFR, KRAS, BRAF, ERBB2 mutations, ALK, ROS1, RET translocations or MET, FGFR1 amplifications in some LCs, have led to discovery of new targeted therapies (1,2,(8)(9)(10)(11)(12)(13)(14) . For this reason, biopsy specimens should be analyzed not only for diagnostic studies, but also maximum amount of tissue should be reserved for molecular studies.…”
Section: Major Molecular Alterations In Lung Cancersmentioning
confidence: 99%
“…Subsequent to ligand-binding, EGFR receptors homo-and heterodimerize and induce autophosphorylation of the intracellular tyrosine kinase domain. Thereafter molecular cascade of events involving in growth, cell proliferation, differentiation, and survival are triggered (10)(11)(12)(13)(14)(15)(16) . Cetuximab, panitumumab, zalutumumab, nimotuzumab, and matuzumab are examples of monoclonal antibodies produced against EGFR receptors (14) .…”
Section: Major Molecular Alterations In Lung Cancersmentioning
confidence: 99%